TOXIC RELATIONSHIP DALAM AL-QUR'AN, STUDI QUR'AN TEMATIK DENGAN PENDEKATAN GROUNDED THEORY - Muhammad Atsiil Al Ahnaf; Muhammad Alif (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2025)
The purpose of this study is to find and analyze the types of harmful relationships from the perspective of the Qur'an. This study uses the Grounded Theory method as a thematic study approach. The types of harmful relationships are types of relationships that are emotionally, spiritually, and socially destructive, which are increasing in modern life, including among Muslims. This study investigates the verses of the Qur'an related to human relationships and the principles of relational morality and finds five main categories of harmful relationships found in the Qur'an: injustice (ẓulm), hypocrisy (nifaq) and emotional manipulation; verbal violence and humiliation of dignity; obstruction of goodness and spirituality (saddu'an sabilillah) and the spread of evil. This study shows that the Qur'an explicitly rejects types of relationships that are not based on rahmah, mawaddah, and taqwa. The results encourage the incorporation of Qur'anic values ​​into relationship education, marriage counseling, and efforts to prevent emotional violence in the family.